2016
DOI: 10.1542/peds.2015-2005
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension Associated With Intravitreal Bevacizumab Therapy for Retinopathy of Prematurity

Abstract: Bevacizumab is an antivascular endothelial growth factor (VEGF) monoclonal antibody, approved as an additional medication with other chemotherapy drugs for the treatment of metastatic cancer. 1 It has been used off-label to decrease retinal thickening in age-related macular degeneration and to diminish intraoperative complications in diabetic retinopathy patients. 2,3 In addition, randomized trials have shown improvement of the retina and reduced zone I disease progression with intravitreal bevacizumab therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 15 publications
(18 reference statements)
1
6
0
1
Order By: Relevance
“…Intravitreal pegaptanib or bevacizumab injection alone or in combination with laser photocoagulation are so far considered as therapeutic modalities for the management of ROP [14] but the systemic toxicity of intravitreal bevacizumab is of concern [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal pegaptanib or bevacizumab injection alone or in combination with laser photocoagulation are so far considered as therapeutic modalities for the management of ROP [14] but the systemic toxicity of intravitreal bevacizumab is of concern [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Als kurzfristige Komplikation nach Anti-VEGF-Therapie wurde eine arterielle Hypotension beschrieben [88]. Zur Frage, ob sich eine Behandlung mit Anti-VEGF-Antikörpern negativ auf die langfristige psychomotorische Entwicklung der Kinder auswirkt, gibt es bislang nur wenige und widersprüchliche Daten [38,54].…”
Section: Intravitreale Injektion Von Anti-vegf-antikörpernunclassified
“…[29] A study by Morin et al reported that severe neurodevelopmental disabilities (Bayley scores <70) was seen 3.1 times higher with bevacizumab compared to laser. [30] Most recently, hypotension-related reports [31] and histopathologically proven new or reactivation of bronchopulmonary dysplasia have been noted after anti-VEGF administration. [32] Few studies were designed to study specific abnormalities related to anti-VEGF treatment and detected no systemic complications.…”
Section: Discussionmentioning
confidence: 99%